TEACHING OF BEHAVIORAL AND EXPERIMENTAL ECONOMICS AND THE PROSPECTS FOR TEACHING IT IN DEVELOPING COUNTRIES: A SURVEY - Sanjaya, Muhammad Ryan (Journal of Indonesian Economy and Business, 2014)
The rising trend of behavioral and experimental economics is observed through a survey ofthe top 100 academic institutions in economics and econometrics. The survey found that thissubject is relatively popular with around 44% of academic institutions offering this course toundergraduate students. Another survey on publication interest found a surge since 2002 thatwas experienced by this subject along with only a few other subjects such as labor economicsand business economics. Lastly, four short experiments on undergraduate students wereconducted in Indonesia to explain economics, and this activity seems to support the studentcenteredlearning that has since became the focus of the Directorate General of HigherEducation in Indonesia.Keywords: behavioral and experimental economics, economics teaching, developing countriesJEL codes: A12, A22, D03